Industrial diagnosis of some agricultural machinery manufacturers in the Philippines a system approach - Jamaluddin, H. H.
A detailed diagnostic study was conducted of the operations of some agri-machinery manufacturers located in different parts of the country. The objective of the study was primarily to characterize weak areas within each firm and to identify problems common to all. Applying the systems approach and considering each of the companies as a system, their performances were studied, appraised and evaluated and a listing of undesirable states within each system was prepared. These evaluations led to the identification of the major problems common to all companies taken as a whole. These common problems (unsatisfactory states) were then subjected to analysis by means of cause and effect diagrams so as to pinpoint the root cause. The root cause was traced to be the "inadequate application of management concepts". Recommendations were then made for removing this root cause and for removing the symptomatic undesirable/unsatisfactory states within each system. A further set of recommendations was made for countering any possible environmental change that could adversely affect these systems. Implementing guidelines were prepared to include a precautionary note on transitory problems that usually come up during implementation. An approximate activity-schedule for the implementation phase was also provided. It was felt from the evaluation of the approach used here that established management audit practices in the Philippines should shift gradually towards using the systems concept and systems approach.